The Application of Participatory Communication in the Implementation of Small Farmers Empowerment Program - Aminah, Sitti (Research and Development Agency Ministry of Home Affairs, 2016)
An agricultural development approach that is centralized, top down, and applied linear communication (transfer of technology) puts farmers as a tool to achieve nationalâs goals (rice self-sufficiency) and makes them dependant to the outsiders. This study aims to analyze the level of participatory communication implementation in the implementation of Small Farmers Empowerment Program. The data are collected using some methods: observation, interview and focus group discussion. The data are analyzed using descriptive statistic. The study result shows that the implementation of participatory communication is in a low category. The recommendations of this study are to enhance the ability of small farmers through increasing the intensity of dialogue between the small farmers and the stakeholders (insiders and outsiders). Exchange of information and knowledg